Original burger (traditional) or burger with mushroom addition? A social representation approach to novel foods - Patinho, Iliani (2021)
Currently, consumers’ interest in healthy products has attracted the attention of academia and the meat industry, which has focused mainly on incorporating ingredients with healthier properties. In this context, the aim of this study was to investigate the social representation of original burgers and burgers with mushroom addition considering different sexes and body mass indexes (BMIs) of individuals. Thus, 209 Brazilians answered a word association task followed by a word classification based on their importance and valence for original burgers and burgers with the addition of mushrooms. To obtain the structure of social representation, the words were positioned into four distinct zones based on their frequency of elicitation and importance. Also, the polarity index was used to give a connotation to the words. Three groups of consumers were identified. The first group (consumers with class-1 obesity of both sexes) associated the original burger with positive categories (cheese, juicy, seasoned, food, tasty, joy, salad and delicious). The second one (female consumers with pre-obesity and class-1 obesity) associated the burger with the addition of mushrooms with the elements price, different, vegetarian, flavor, gourmet and healthy. Finally, the third group (men and women for both stimuli and with a wide range of BMI) characterized burgers with sensory attributes, feelings and moments of consumption. In conclusion, the social representation of the original burger and the burger with the addition of mushrooms differed among consumers, suggesting that the main associations can be the main motivations for the consumption of a certain product.